KONTRIBUSI SEKTOR PAJAK KENDARAAN BERMOTOR TERHADAP INFRASTRUKTUR JALAN DI PROVINSI SULAWESI TENGGARA - Muhammad Usman Silo; La Ode Geo; LM Harafah (Jurnal Perencanaan Wilayah, 2018)
This study aims to analyze; 1) the performance of increased availability of infrastructure and anincrease in motor vehicle tax revenues every year in Southeast Sulawesi Province; and 2) the role ofincreasing motor vehicle tax receipts on infrastructure improvements in Southeast Sulawesi Province. Thisresearch was carried out at the Revenue Service office, the Southeast Sulawesi Provincial Public WorksOffice, and the SAMSAT offices throughout the districts / cities in Southeast Sulawsei Province. Dataanalysis performed was descriptive qualitative method and simple regression.The results of the study show that; 1) the contribution of the motor vehicle tax sector every yearto 12 districts / cities in Southeast Sulawesi Province is quite varied, and Kendari City is the biggestcontributor to PKB income and the lowest contribution is North Buton Regency; 2) During the period 2018-2015 the construction of road infrastructure (the length of the road built) was around 601.12 Km (10.24%),where the South Konawe Regency had the longest road length of 88.32 Km, while the construction of theshortest road was in Kabupaten Bombana namely 18.68 Km; and 3) the contribution (amount of revenue) ofthe PKB does not have a significant effect on the development of road infrastructure in Southeast SulawesiProvince so that the length of the road to be built in the future is around 5,270.75 Km, with a growth rate of10.24%. .Keywords: Contributions, Motor Vehicle Taxes and Road Infrastructure